GRP78/Dna K Is a Target for Nexavar/Stivarga/Votrient in the Treatment of Human Malignancies, Viral Infections and Bacterial Diseases. Issue 10 (October 2015) - Roberts, Jane L.; Tavallai, Mehrad; Nourbakhsh, Aida; Fidanza, Abigail; Cruz‐Luna, Tanya; Smith, Elizabeth; Siembida, Paul; Plamondon, Pascale; Cycon, Kelly A.; Doern, Christopher D.; Booth, Laurence; Dent, Paul
<x xml:space="preserve">Abstract</x> Prior tumor cell studies have shown that the drugs sorafenib (Nexavar) and regorafenib (Stivarga) reduce expression of the chaperone GRP78. Sorafenib/regorafenib and the multi‐kinase inhibitor pazopanib (Votrient) interacted with sildenafil (Viagra) to further rapidly reduce GRP78 levels in eukaryotes and as single agents to reduce Dna K levels in prokaryotes. Similar data were obtained in tumor cells in vitro and in drug‐treated mice for: HSP70, mitochondrial HSP70, HSP60, HSP56, HSP40, HSP10, and cyclophilin A. Prolonged 'rafenib/sildenafil treatment killed tumor cells and also rapidly decreased the expression of: the drug efflux pumps ABCB1 and ABCG2; and NPC1 and NTCP, receptors for Ebola/Hepatitis A and B viruses, respectively. Pre‐treatment with the 'Rafenib/sildenafil combination reduced expression of the Coxsackie and Adenovirus receptor in parallel with it also reducing the ability of a serotype 5 Adenovirus or Coxsackie virus B4 to infect and to reproduce. Sorafenib/pazopanib and sildenafil was much more potent than sorafenib/pazopanib as single agents at preventing Adenovirus, Mumps, Chikungunya, Dengue, Rabies, West Nile, Yellow Fever, and Enterovirus 71 infection and reproduction. 'Rafenib drugs/pazopanib as single agents killed laboratory generated antibiotic resistant E. coli which was associated with reduced Dna K and Rec A expression. Marginally toxic doses of 'Rafenib drugs/pazopanib restored antibiotic sensitivity in pan‐antibiotic resistant bacteria including multiple strains of blakpcKlebsiella pneumoniae. Thus, Dna K is an antibiotic target for sorafenib, and inhibition of GRP78/Dna K has therapeutic utility for cancer and for bacterial and viral infections. J. Cell. Physiol. 230: 2552–2578, 2015. © 2015 Wiley Periodicals, Inc.